“[…] cariche de perle tanto argente non ha Milano, Cremona ne Ferrara insieme” – Tessuti liturgici medievali ricamati con perle nel Tesoro della Cattedrale di Esztergom - Szabó, Ágnes (Verbum – Analecta Neolatina, 2022)
Modenese cleric, Giovanni Maria Parenti, member of the entourage of young Ippolito d’Este arriving in Hungary in 1486 mentions the treasuries of Esztergom Cathedral in his diary. On the basis of his statements, this study aims to collect all written sources, mainly inventories of the former treasury of the Cathedral, referring to pearl embroidered liturgical textiles in order to recognize the volume and type of pearl embroidered paraments in Hungary’s oldest treasury. Besides the Esztergom registers, the investigation reckons with the existing inventories of Late Medieval Hungary’s ecclesiastic centres to reveal the phenomenon of pearl embroidered garments in a wider geographical context. The study is a first step of widespread research in the field of Central-European pearl liturgical textiles from the Middle Ages.